A game theoretic approach to collaboration in policy coordination - Eleonora Herrera Medina; Antoni Riera Font (Economies, 2023)
Public policies are courses of action by a government in response to public problems in the real world with the aim of meeting the needs of society. Such policies must be coordinated to avoid inefficiencies. Most attempts to model public policy coordination are qualitative and, therefore, do not yield precise conclusions. More accurate modelling attempts are found in game theory, but they are not entirely appropriate as models of policy coordination, because policy coordination involves a high degree of collaboration. There is only one game-theoretic model of collaboration, and it does not model public policy coordination. The aim of this article is to show that a collaboration-based game theory model is not only feasible, but also more realistic than current game theory models of policy coordination. This was performed by adapting Newton's seminal model to a society capable of formulating and coordinating policies. When this adapted game was compared to alternative games used to explain policy coordination, it was found that the adapted game made more realistic assumptions, the modelling process was simpler, and it can be applied to a broader range of contexts. By demonstrating that the adapted model offers a feasible theoretical foundation for the modelling of policy coordination, this paper provides a starting point for future modelling efforts in this area.
Keywords: 330; collaboration; policy coordination; public policy; evolution; mutualistic behaviour